Costumbres y tradiciones autóctonas en el turismo cultural del cantón Mocache, año 2019 - Alvarado Alvarado, Arelis Adriana (2019)
The customs and traditions of the Mocache canton have been affected by the scarce information and use of cultural resources, as well as the lack of knowledge of the place as a cultural value. The inhabitants of Mocache have maintained their culture for many years, but at the same time it has been affected by an effect called syncretism, especially in young people since they are losing their identity, in addition they are losing some ancestral knowledge due to the little practice of Fortunately, the canton has a unique culture in the world to develop cultural tourism, as this is increasing but not in its entirety, the canton also has an unparalleled cultural wealth, its festivities have great wealth in each of its dances, clothing and beverages, it should be noted that tourism in this place is under development so there are not enough tourist attractions, but adequate for the provision of services to local and national tourists. The indigenous customs and traditions contribute to cultural tourism, but in the canton it is little known due to the lack of publicity on the part of the authorities since it does not have the necessary information, therefore it has not been possible to develop cultural tourism. The main objective of the proposed thesis is to propose a promotional plan on the various local customs and traditions and their contribution to cultural tourism as an opportunity to recover and disseminate them for local people and visitors to know. Through a good diffusion of the customs and traditions, it will be possible to maintain and preserve this culture to the current generations, so that they are the exponents of these events that will give the necessary value to the Mocacheña culture, increasing the development of the Cultural tourism benefiting the inhabitants of the communities improving the quality of life. After going to books, internet sources and other means, which would allow obtaining necessary information for the elaboration of this project, the research carried out was exposed in each one of the pages.